UTILIZATION OF JAMU IN PUERPERAL MOTHER IN SUMATERA AND JAVA ISLAND (LITERATURE REVIEW OF HEALTH ETHNOGRAPHIC RESEARCH 2012-2016) - Zulfa Auliyati Agustina; Yunita Fitrianti (The Indonesian Journal of Public Health, 2020)
ABSTRACTIndonesian people used to consume herbal medicines called "jamu", which is as a hereditary alternative medicine, to heal or fresh the body. Furthermore, the postpartum mother, who needs recovery after birth, also drinks the herbs. This essay employed a literature review of 14 ethnographic books conducted by National Institute of Health Research and Development, which focused on the herbal medicines for puerperal mothers. The results of the literature review revealed that the majority of mothers in Java and Sumatera using jamu during the postpartum period to heal and recover the mother's health. Not only do the mother drink jamu, but she also applies certain herbs on her body. Clinical trials have proved the efficacy of ingredients for herbal medicines. Therefore, people prefer to use the herbs because it is easy to find and inexpensive, and it also has a long-term effect on the mother's health and fitness. However, herbal medicine, which is usually employed by the people, needs further research, in particular, the dose of jamu. So, herbal medicine based on local wisdom can be one of consideration in the health development program. Keyword: Jamu, Pueperal, Traditional